2021
DOI: 10.1103/physreva.103.013318
|View full text |Cite
|
Sign up to set email alerts
|

Functional renormalization for repulsive Bose-Bose mixtures at zero temperature

Abstract: We study weakly-repulsive Bose-Bose mixtures in two and three dimensions at zero temperature using the functional renormalization group (FRG). We examine the RG flows and the role of density and spin fluctuations. We study the condition for phase separation and find that this occurs at the mean-field point within the range of parameters explored. Finally, we examine the energy per particle and condensation depletion. We obtain that our FRG calculations compare favorably with known results from perturbative app… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 79 publications
(136 reference statements)
2
16
0
Order By: Relevance
“…Indeed, we have found that we obtain similar agreements for other choices of |a AB /a| < 1. Note that the case a AB = 0 simply reduces the problem to two independent [81].…”
Section: Balanced Bose-bose Gasesmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, we have found that we obtain similar agreements for other choices of |a AB /a| < 1. Note that the case a AB = 0 simply reduces the problem to two independent [81].…”
Section: Balanced Bose-bose Gasesmentioning
confidence: 99%
“…In this work, we provide a detailed presentation of the FRG formalism for weaklyinteracting Bose-Bose mixtures to motivate further FRG studies. To illustrate this approach, we examine thermodynamic properties of three-dimensional attractive and repulsive mixtures at both zero and finite temperatures, going beyond what was presented in our previous works [81,82]. Even though we do not explore new physics in this work, we narrow exciting new directions where the FRG could provide more robust descriptions than currently used approaches.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this work, we provide a detailed presentation of the FRG formalism for weaklyinteracting Bose-Bose mixtures to motive further FRG studies. To illustrate this approach, we examine thermodynamic properties of three-dimensional attractive and repulsive mixtures at both zero and finite temperatures, going beyond what was presented in our previous works [78,79]. Even though we do not explore new physics in this work, we narrow exciting new directions where the FRG could provide more robust descriptions than currently used approaches.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, stronglycorrelated lattice systems have been studied with both fermionic [75] and bosonic [76,77] atoms. Recently, some of us have successfully applied the FRG to the study of both balanced repulsive Bose-Bose mixtures [78] and strongly-interacting Bose polarons [79], both in homogeneous configurations at zero temperature. These results make the FRG a promising approach to give a consistent and unified description of Bose-Bose gases and Bose polarons.…”
Section: Introductionmentioning
confidence: 99%